Investigations on In₀.₁₂Al₀.₈₈N/AlN/AlₓGa₁−ₓN/In₀.₁₂Al₀.₈₈N MOS-HFETs With Symmetrically-Graded Wide-Gap Channel and Drain Field-Plate Design - Jian-Hong Ke; Ching-Sung Lee; Han-Yin Liu; Jung-Hui Tsai; Wei-Chou Hsu (IEEE Access, 2024)
Novel In0.12Al0.88N/AlN/AlxGa $_{1-x}\text{N}$ /In0.12Al0.88N metal-oxide-semiconductor heterostructure field-effect transistors (MOS-HFETs) grown on a SiC substrate with a drain field-plate (DFP) were investigated. A symmetrically-graded AlxGa $_{1-x}\text{N}$ (x = $0.32~→ ~0.1~→ ~0.32$ ) wide-gap channel with an In0.12Al0.88N back-barrier was devised to enhance the carrier confinement, channel conductivity, and breakdown characteristics. The MOS-gate structure, employing high-k Al2O3 gate dielectric and surface passivation deposited by the non-vacuum ultrasonic spray pyrolysis deposition (USPD) technique, has resulted in enhanced gate modulation and decreased gate leakage current. A control MOS-HFET (sample A) with an equivalent Al0.21Ga0.79N channel and DFP was fabricated in comparison with the present design without/with DFP (samples B1/B2). The present sample B2 (A) has demonstrated a superior maximum drain-source current density ( $I_{DS, max}$ ) of 937.4 (838.8) mA/mm, maximum extrinsic transconductance ( $g_{m, max}$ ) of 89.6 (80.6) mS/mm, on/off-current ratio ( $I_{on}/I_{off})$ of $1.8× 10^{8}$ ( $1.3× 10^{8}$ ), two-terminal off-state gate-drain breakdown voltage ( $BV_{GD}$ ) of −530 (−490) V, three-terminal on-state drain-source breakdown voltage ( $BV_{DS}$ ) of 520 (465) V at 300 K, and the corresponding Baliga’s figure-of-merit (BFOM) of 79.5 (39.3) MW/cm2. The present design is promising for high-voltage power-switching circuit applications.